(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
This paper explores information literacy education (ILE) through a school project work in selected Malaysian schools. This qualitative study investigates how IL is taught by teachers and experienced by students on a big scale,nationwide-standardized school project. The research participants were five history teachers and twenty-three students from four schools. The data collection techniques employed were teacher’s individual interview; students’ focus group interview; document analysis (project journal and project report); and classroom observation. The findings show that while teachers employ five different teaching techniques to facilitate the students with their project, these efforts were geared towards accomplishing a predetermined learning output, rather than guiding students on how to do research. Teachers relied heavily on project guidelines to help the students produce a pre-determined project report, suggesting shallow research instruction. Results on students’ project experience similarly reveal compelling evidence of students’ preoccupation with the project guideline to produce their report. They only employed basic searching strategies and did not explore more sophisticated search techniques. The students used information mainly from the Internet resources that directly answered their project questions, and did not evaluate or filter information as suggested by IL models. They also were found to have serious problems concerning the ethical use of information. Further findings suggest that IL was not adequately delivered and integrated by teachers in classrooms. The findings are hoped to provide baseline information on IL development in less-developed countries where IL awareness is still minimal.